Sounding the self : analogy in improvisational music therapy - Smeijsters, Henk (Barcelona Publishers, 2005)
A general theory on the role of analogy in music therapy, explaining how a person can use music to "sound" his or her Self, and how the Self interacts with the environment. The values of analogy are examined in terms of the differences between representing human experience through language versus music. The author demonstrates how the concept of analogy can be used in formulating treatment goals and interventions, evaluating the effectiveness of treatment, and developing rationales about treatment and effectiveness. Qualitative research is advocated.
Keywords: Music therapy : Research